Teachers’ Professional Competence and Student Character as Predictors of Academic Achievement in Indonesian Elementary Schools: A Quantitative Ex Post Facto Study - Misnawati Misnawati; Tri Widayatsih; Muhammad Fahmi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the influence of teacher professional competence and student character on academic achievement in public elementary schools in Banyuasin District, Indonesia. A quantitative ex post facto design was employed, with 86 teachers selected via proportionate stratified random sampling. Data were collected using validated Likert-scale questionnaires, observation sheets, and report card documentation, then analyzed using multiple linear regression. Descriptive results indicated that teacher professional competence and student character were categorized as high, and student achievement was good, with all prerequisite tests (normality, linearity) satisfied. Partially, teacher professional competence significantly predicted student achievement (t = 102.32, p < 0.001), contributing 66.1%; student character also significantly predicted achievement (t = 101.61, p < 0.001), contributing 80%. Simultaneously, both variables explained 80% of the variance in student achievement (adjusted R² = 0.800, F = 4897.94, p < 0.001). The study concludes that teacher competence and student character function synergistically to enhance academic outcomes, with student character showing a slightly stronger predictive contribution. The novelty lies in empirically demonstrating the near-equal and substantial combined predictive power of both variables within the underexplored context of Indonesian public elementary schools, moving beyond isolated examinations of each factor. Practically, these findings suggest that schools should invest equally in professional development programs for teachers and character education initiatives for students to maximize academic achievement. This study contributes to educational psychology and school management literature by providing robust quantitative evidence that academic success is co-determined by instructional quality and student non-cognitive attributes, highlighting the need for integrated interventions addressing both domains simultaneously.